Optimization of Processing Conditions and Level of Extenders Used for the Preparation of Extended Restructured Mutton Chops - Sharma, Heena; Mendiratta, S.K.; Sharma, B.D.; Talukder, Suman; Giriprasad , R. (Journal of Meat Science, 2014)
Appropriate binding of meat pieces and high water retention are two most important factors in marketing high quality processed meat products. Here, the non-meat ingredients play pivotal role and can improve the appearance, palatability and texture of the finished products. In this experiment, processing conditions viz., massaging time (8 min, 10 min and 12 min) and cooking time (35 min, 40 min and 45 min) as well as the level of extenders viz., pea hull flour (3%, 4% and 5%) and boiled and mashed potato (3%, 4% and 5%) were studied at different levels to see the effect on sensory attributes. Massaging times did not significantly influence the sensory scores but 10 min of massaging time was optimum. Sensory scores at cooking time of 45 min were significantly higher (P
Keywords: Restructured mutton chops; Massaging time; Cooking time; Peahull flour; Potato; Extenders